Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:The Role of Knowledge Management in Achieving the Sustainable Competitive Advantage  for Secondary Schools in Riyadh CityMs. Nouf Hameed AlmohammadiThe Reality of Digital Transformation in Jordanian Schools from the Point of view of TeachersMs. Marwa Mohammad Al-Qatarneh ,Dr. Fatima Abd Alkareem WahbaThe role of bilingual education in promoting cultural diversity among school students  In the Interior of Palestine from the Teachers’ PerspectiveMs. Shireen Saed AbbasReasons for the Decline in the Planning Standard in School Evaluation Results: from the Perspective of School Principals in the Tan’eem Education Office, MakkahMr. Ali Atiyah Ali Al-MalkiResearch trends related to the role of artificial intelligence in improving blended learning practices at the undergraduate levelMs. Ghzail Fahad Aldossari, Ms. Sarah Misha'i Al-DosariDifficulties Facing Strategic and Educational Planning in the Ministry of Education  in Palestine stateMr. Mahmoud Hoseen AlajjouriPsychometric Properties of the Stress Coping Strategies Scale for AdolescentsMr. Muhammad Yahya Al-Hazzazi, Prof. Saleh Yahya Al-Ghamdi
Keywords: Journal of Educational and Psychological Sciences